2020
DOI: 10.1111/epi.16730
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the electrophysiological border between hypothalamic hamartomas and the hypothalamus for the target of ablation surgery identified by intraoperative semimicrorecording

Abstract: Objective: Ablation surgery has become the first line of treatment for hypothalamic hamartomas (HHs). For effective treatment, optimum targeting of ablation is mandatory. The present study aimed to evaluate the correspondence between the electrophysiological features of HHs and morphological targeting by semimicrorecording during stereotactic radiofrequency thermocoagulation (SRT). Methods: Eighty HH patients who underwent SRT were involved. Semimicrorecording was performed on the first trajectory. The distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…18,19 Studies by Sonoda et al 20 and Hamdi et al 21 were also excluded since they reported cognitive results rather than epilepsy outcomes after HH treatment. Four articles [22][23][24][25] were excluded because of duplicated data with the study by Shirozu et al 26 Only 7 patients from Abla et al 27 and 6 from Mathieu et al 28 were included because other procedures were performed during the follow-up period. A patient from the study by Du et al 29 was excluded because of the absence of seizures at HH presentation.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Studies by Sonoda et al 20 and Hamdi et al 21 were also excluded since they reported cognitive results rather than epilepsy outcomes after HH treatment. Four articles [22][23][24][25] were excluded because of duplicated data with the study by Shirozu et al 26 Only 7 patients from Abla et al 27 and 6 from Mathieu et al 28 were included because other procedures were performed during the follow-up period. A patient from the study by Du et al 29 was excluded because of the absence of seizures at HH presentation.…”
Section: Resultsmentioning
confidence: 99%
“…The T2-STIR sequence was used to discriminate the white matter fibers from the HH body in this planning protocol. The primary goal of this procedure was full disconnection between the lesion and normal brain tissue [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative enhanced T1 images obtained immediately after the ablation (repetition time (TR) = 2300 ms, echo time (TE) = 2.3 ms, slice thickness = 1 mm, voxel size = 1 mm × 1 mm × 1 mm) and preoperative MRI scans were fused to construct a 3D model of the actual ablation area, with the ablation rate being defined by the percent of HH body ablated. A 3D model of the connected region was also generated as follows: Initially, T1 images were rotated around to Z-axis to ensure that the HH border was parallel to the X-axis, with this border being defined by the intensity or angle differences of the third ventricle wall [ 12 ]. Then, three consecutive slices from the border to the HH body were selected and used to outline the edges of the connected part, thereby yielding a 3D model.…”
Section: Methodsmentioning
confidence: 99%
“… 53 , 54 The unique electrophysiologic characteristics of both the HH and the nearby normal hypothalamus were also studied, and those findings potentially correlated with the area to be resected/disconnected. 55 …”
Section: Geneticsmentioning
confidence: 99%